2015
DOI: 10.1007/s00018-015-1967-2
|View full text |Cite
|
Sign up to set email alerts
|

Roles of connexins and pannexins in (neuro)endocrine physiology

Abstract: To ensure appropriate secretion in response to demand, (neuro)endocrine tissues liberate massive quantities of hormones, which act to coordinate and synchronize biological signals in distant secretory and nonsecretory cell populations. Intercellular communication plays a central role in this control. With regard to molecular identity, junctional cell-cell communication is supported by connexin-based gap junctions. In addition, connexin hemichannels, the structural precursors of gap junctions, as well as pannex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 158 publications
(242 reference statements)
1
25
0
Order By: Relevance
“…Indeed, early ultrastructural investigations of the pineal in mammals have described gap junction formation either between pinealocytes, between pineal astrocytes and between interstitial cells in various species, including rat (Krstic, ; Taugner et al ., ; Ceiciura & Krakowski, ), guinea pig (Huang & Taugner, ), rabbit (Romijn, ), monkey (Ichimura, ; Ichimura et al ., ) and humans (Moller, ). In accordance with these observations, several connexins were reported to be expressed in the pineal (Hodson et al ., ). These include connexin36 (Cx36) in rat pinealocytes (Belluardo et al ., ; Condorelli et al ., ), connexin26 (Cx26) in rat pinealocytes (Saez et al ., ; connexin43 (Cx43) in rat pineal astrocytes (Saez et al ., ; Berthoud & Saez, ), and Cx43 together with Cx45 in various pineal cell types in chicken (Berthoud et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, early ultrastructural investigations of the pineal in mammals have described gap junction formation either between pinealocytes, between pineal astrocytes and between interstitial cells in various species, including rat (Krstic, ; Taugner et al ., ; Ceiciura & Krakowski, ), guinea pig (Huang & Taugner, ), rabbit (Romijn, ), monkey (Ichimura, ; Ichimura et al ., ) and humans (Moller, ). In accordance with these observations, several connexins were reported to be expressed in the pineal (Hodson et al ., ). These include connexin36 (Cx36) in rat pinealocytes (Belluardo et al ., ; Condorelli et al ., ), connexin26 (Cx26) in rat pinealocytes (Saez et al ., ; connexin43 (Cx43) in rat pineal astrocytes (Saez et al ., ; Berthoud & Saez, ), and Cx43 together with Cx45 in various pineal cell types in chicken (Berthoud et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The latter have been shown to form exceptionally long-range functional networks that have been postulated to act in the transduction of signals between distant endocrine cell populations 10 . Apart from the direct cell–cell interactions, which are largely mediated through gap junctions 11 , a complex array of paracrine signals serve to modulate pituitary cell activity, thus presenting an additional regulatory pathway in which pituitary cells interact to produce physiologically accurate output 12 .…”
mentioning
confidence: 99%
“…In the context of arrhythmias, an interesting question arises as to whether TCA patients during follow-up exhibit some specific risk factors for cardiac arrhythmias, such as the pro-arrhythmic β1-adrenergic and M2 muscarinic receptor autoantibodies or changes in the myocardial connexins. It has been shown that TSH and TH regulate the expression of connexins in a variety of target tissues, including the thyroid gland [159]. Reduced connexin-43 expression in the thyroid tissue differentiates TCA from a benign disease and provides clinical utility as a marker for malignancy [160,161], while decreased connexin-43 protein abundance in the cardiac tissue in the experimental hyperthyroid setting increases the propensity to AF and VF [26,27,108,162].…”
Section: Cellular and Molecular Actions Potentially Involved In Pro-amentioning
confidence: 99%